CORPORATE SOCIAL RESPONSSIBILITY IN TERMS OF COVID 19 PANDEMIC - Delev, Jordan (International Scientific Journal Vision, 2020)
Global society is currently facing the greatest challenge of the 21st century. The pandemic created by the Sars-Cov-2 virus has caused a major health crisis which has appropriate implications not only for health organizations and institutions, but also for the whole institutional system of each country and particularly has a full impact on the functioning of national legal and economic systems. The COVID 19 pandemic expresses its health, legal and economic repercussions equally to all social actors. Analyzed from a legal and economic point of view, legal entities, companies are equally exposed to the effects of the pandemic as individuals (natural persons). The companies strive to achieve their lucrative goal, but in parallel with the lucrative goal, they should also provide their social component, i.e. to contribute to the development of the community in which they operate and function. The purpose of this paper is, using the method of analysis to determine the basic need for corporate social responsibility, especially in the presence of the COVID 19 pandemic. The analysis comes down to defining corporate social responsibility and the impact of the pandemic on the performance of its functions. In that regard, within the newly created economic conditions of functioning, the need to use corporate social responsibility as an element of the business policy of companies and implementation of soft law practices was analyzed. The paper includes an appropriate analysis of the applicability of corporate social responsibility in the new conditions. On the other hand, the use of the comparative method provides a comparison of examples from world and Macedonian practice. The focus of the paper is on emphasizing the need for a responsible approach of companies and realization of the defined corporate social responsibility in changed conditions imposed by the COVID 19 pandemic.